Exploring the Nexus of Work-Life Balance Sub-Factors and Job Satisfaction: A Study on Executives in the Commercial Banking Sector - Nurasnida Miswadi; Aida Azlina Mansor (Information Management and Business Review, 2023)
This research paper aims to investigate the relationship between work-life balance and job satisfaction among executives in the commercial banking sector. The study considers three sub-factors of work-life balance, namely flexible work arrangements, organizational culture, and motivation, to analyze their impact on employee job satisfaction. Questionnaires were distributed to executives in a commercial bank located in Johor Bahru, resulting in 213 responses. The collected data confirmed the relationship between the examined constructs and provided support for the hypothesized relationships of work-life balance sub-factors with job satisfaction. The study emphasizes the importance of analyzing and enhancing work-life balance through flexible working arrangements, motivation, and organizational culture to promote job satisfaction and maximize human capital resources within organizations. The outcomes of this study can serve as a benchmark for management seeking to improve job satisfaction levels among employees. Notably, while previous research has explored work-life balance, limited attention has been given to its subtopics and their impact on job satisfaction within commercial banks. This study addresses these gaps in understanding and provides valuable insights into work-life balance and job satisfaction in the banking sector.